Understanding inter-individual variability in pharmacokinetics/pharmacodynamics of aripiprazole in children with tic disorders: Individualized administration based on physiological development and CYP2D6 genotypes - Xin, Yingying; Gao, Liuliu; Tuo, Yali; Nie, Gang; Mei, Yan; Chen, Chen; Wang, Jun; Li, Sichan; Sun, Dan; Qian, Qiaoqiao; Fu, Yongli; Wang, Yang; et al. (Frontiers in Pharmacology, 2022)
Objective: This study aims to develop a combined population pharmacokinetic (PPK) model for aripiprazole (ARI) and its main active metabolite dehydroaripiprazole (DARI) in pediatric patients with tic disorders (TD), to investigate the inter-individual variability caused by physiological and genetic factors in Pharmacokinetics/Pharmacodynamics of ARI and optimize the dosing regimens for pediatric patients. Methods: A prospective PPK research was performed in Chinese children with TD. A total of 84 patients aged 4.83 - 17.33 years were obtained for the pharmacokinetic analysis. All patients were genotyped and phenotyped based on the detection of 27 CYP2D6 gene alleles. Goodness-of-fit, bootstrap, visual prediction (VPC) and normalized prediction distribution errors (NPDE) tests were used to evaluate the prediction performance of the PPK model. Moreover, the clinical efficacy was evaluated according to reduction rate of Yale Global Tic Severity Scale (YGTSS) score at the 12th week comparing with the baseline. The relationship between the exposure of ARI and clinical efficacy was investigated and Monte Carlo simulations were used to evaluate and optimize dosing regimens. Results: The PPK model was established to predict the concentrations of ARI and DARI. Body weight and CYP2D6 genotype were the significant covariates affecting the clearance of ARI. The DARI/ARI metabolic ratios (MRs) of AUC24h, Cmin and Cmax at the steady state of results demonstrated that ultra-rapid metabolizers (UMs) > normal metabolizers (NMs) > intermediated metabolizers (IMs). The diagnostic cut-off points of MRs were identified respectively and it could be used to distinguish UMs or IMs from other patients. The response rate of ARI was 73% after 12 weeks of treatment. The receiver operating characteristic (ROC) analysis results suggested that the best predictor of clinical efficacy for children with TD was the trough concentration of ARI and the cut-off point was 101.636 ng/mL. Finally, the optimal dosage regimens were proposed on the basis of different body weight and CYP2D6 genotypes. Conclusions: The pharmacokinetics of ARI and DARI in pediatric patients with TD were significantly influenced by body weight and CYP2D6 genotype. Individualized dosing regimens were recommended for pediatric patients with TD to ensure clinical efficacy.